Penyuluhan Kesehatan Alat Reproduksi Untuk Mencegah Pernikahan Dini Dan Menciptakan Generasi Baik - Cemara, Dita; Fajri, Rizki; Febrilestari, Risky; Huda, Nurul; Pepsaklin D, Usolihati (UIR Press, 2024)
Service activities through Real Work Lectures (KKN) which involve screening and counseling regarding reproductive organs for teenagers are an important initiative to identify health risk factors, including nutritional problems, reproductive health and mental health, which are often not detected at an early stage. This activity also aims to increase knowledge and awareness regarding reproductive health among the younger generation. The methods used in this KKN service activity include comprehensive and targeted health examinations, as well as conveying information through presentations, interactive discussions, and distribution of interesting educational materials. The results of this activity show a significant increase in teenagers' knowledge about the importance of health. It is hoped that this service activity can encourage teenagers to be more proactive in maintaining their health and gain better access to necessary health services, as well as empowering them to make better decisions regarding reproductive health and build healthy relationships. Further research is needed to assess the long-term impact of this education on adolescent reproductive health and behavior.